PENGARUH SUPERVISI DAN MOTIVASI KERJA TERHADAP KUALITAS PENDIDIKAN SEKOLAH DASAR NEGERI DI KECAMATAN MAKASAR JAKARTA TIMUR - DARYANTI DARYANTI (Jurnal Manajemen Pendidikan, 2013)
This research aims to find out (1) the influenced of supervision toward work motivation (2) the influenced of work motivation toward education quality (3) the influenced of supervision toward education quality. The research method used is the survey by path analysis. This research was carried out in Kecamatan Makasar East Jakarta. Research findings are outlined as follows (1) there is a direct and significant influenced of supervision toward work motivation (2) there is a direct and significant influenced of work motivation toward education quality (3) there is a direct and significant influenced of supervision toward education quality.